Alterações estruturais na economia goiana e do sudoeste de goiás no período dos anos 80/90 - Pereira, Sebastião Lázaro (2001)
Structural changes in the economy of the Southwest of Goiás and Goiás State were analyzed as a result of changes in the Brazilian development style, especially those resulting from trade and financial openings, as well as deregulation. The analysis was performed using the following instruments: authors' contribution reading to understand the changes the Brazilian economy went through; collection of statistical data to verify significant variations in income at the three levels, federal, state and municipal; Survey of complementary data to help understand the changes at the regional level of aggregation. It was identified that the transformations of the 1990s altered the generation of wealth in the state of Goiás and in the southwest of Goiás, because they presented locational advantages for the capitals and entirely southwest of Goiás the municipality of Rio Verde was the most benefited. This municipality has benefited from the locational and comparative advantages that are most advantageous for the capital within the new style of development.